Protein Arginine Methyltransferase 5 Functions via Interacting Proteins - Liang, Zhenzhen; Wen, Chaowei; Jiang, Heya; Ma, Shumei; Liu, Xiaodong (Frontiers in Cell and Developmental Biology, 2021)
The protein arginine methyltransferases (PRMTs) are involved in such biological processes as transcription regulation, DNA repair, RNA splicing, and signal transduction, etc. In this study, we mainly focused on PRMT5, a member of the type II PRMTs, which functions mainly alongside other interacting proteins. PRMT5 has been shown to be overexpressed in a wide variety of cancers and other diseases, and is involved in the regulation of Epstein-Barr virus infection, viral carcinogenesis, spliceosome, hepatitis B, cell cycles, and various signaling pathways. We analyzed the regulatory roles of PRMT5 and interacting proteins in various biological processes above-mentioned, to elucidate for the first time the interaction between PRMT5 and its interacting proteins. This systemic analysis will enrich the biological theory and contribute to the development of novel therapies.